New concepts in neurology education: successful implementation of flipped classroom lectures - Katharina Mosene; Henrik Heitmann; Dennis Pötter; Friederike Schmidt-Graf (Neurological Research and Practice, 2022)
Abstract In order to inspire and attract young people to Neurology, we must offer high-quality and attractive teaching! To improve neurological education at our Medical School (Technical University of Munich), we converted the main lecture into an e-learning concept using a flipped classroom model. Students had to prepare with a video and a text as well as answering multiple choice questions before each lecture. As a further incentive, students with ≥ 80% right answers in multiple choice questions received a bonus for the final exam. During the lectures, predominantely patient cases were discussed to apply, improve and enhance the previously acquired knowledge. The realignment of the main lecture in Neurology into a flipped classroom model was very successful and was further optimized in the following semesters based on the evaluations obtained for the new concept. Moreover, this enabled us to quickly switch to remote teaching during the COVID-19 pandemic, while still offering lectures of high quality. In addition, this new teaching concept attracts students for Neurology. Furthermore, the exemplary conversion of the Neurology main lecture to a flipped classroom concept also serves as best practice and motivation to adapt other courses in our faculty and far beyond.